Bibliografia Ziemi Lubuskiej 1945-2021. Realizacje, wyzwania, problemy = Bibliography of the Lubusz Region 1945-2021.Realizations, challenges and problems - Urbaniak. Anna (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The article aims to characterize the resources of the Bibliography of the Lubusz Region, created by the bibliographic team of the Regional and Bibliographic Information Department of the Cyprian Norwid Regional and City Public Library in Zielona Góra. It focuses on the problems and challenges connected with updating and merging the collection into a homogenous electronic database, developed according to the latest cataloguing standards in the MARC 21 format.
Keywords: bazy danych; bibliografie regionalne; Deskryptory Biblioteki Narodowej; nagłówki tematyczne; implamantacja; karty katalogowe; katalogowanie; klasyfikacja regionalna; konwersja; MARC21; bibliographic description; development; rekord bibliograficzny; Ziemia Lubuska; databases; regional bibliography; National Library Descriptors; subject headings; implementation; card catalogue; cataloguing; local classification; conversion; MARC 21; bibliographic record; Lubusz Land